Meaning Discrimination in Bilingual Venda Dictionaries - Mafela, Munzhedzi James (Lexikos, 2005)
ABSTRACT: Venda, one of the minority languages in South Africa, has few dictionaries. All are translational bilingual dictionaries meant for dictionary users who are non-native speakers of the language. Dictionary users find it difficult to use the bilingual Venda dictionaries because they are confronted with equivalents which they cannot distinguish. In most cases, the equivalents of the entry-words are provided without giving meaning discrimination. Without a good command of Venda and the provision of meaning discrimination, users will find it difficult to make a correct choice of the equivalent for which they are looking. Bilingual Venda dictionaries are therefore not helpful for dictionary users who are non-native speakers of the language. Devices such as giving illustrative examples, indicating parts of speech and adding etymology could be used to solve the problem of meaning discrimination in bilingual Venda dictionaries. This article highlights the problem of the absence of meaning discrimination and suggests solutions to future Venda lexico-graphers in this regard.Keywords: BILINGUAL DICTIONARY, MEANING DISCRIMINATION, EQUIVALENCE, ENTRY-WORD, LEXICOGRAPHY, CULTURE, TRANSLATION, SOURCE LANGUAGE, TAR-GET LANGUAGE, SYNONYM, POLYSEMY*****OPSOMMING: Betekenisonderskeiding in tweetalige Vendawoordeboeke. Venda, een van die minderheidstale in Suid-Afrika, het min woordeboeke. Almal is vertalende tweetalige woordeboeke bedoel vir woordeboekgebruikers wat nie moedertaalsprekers van die taal is nie. Woordeboekgebruikers vind dit moeilik om tweetalige Vendawoordeboeke te gebruik om-dat hulle gekonfronteer word met ekwivalente wat hulle nie kan onderskei nie. In die meeste gevalle word die ekwivalente van die trefwoorde verskaf sonder om betekenisonderskeiding aan te dui. Sonder 'n goeie beheersing van Venda en die aanduiding van betekenisonderskeiding, sal gebruikers dit moeilik vind om die regte keuse van die ekwivalent waarvoor hule soek, te maak. Tweetalige Vendawoordeboeke is dus nie van hulp vir woordeboekgebruikers wat nie moedertaal-sprekers van die taal is nie. Middele soos die gee van ophelderende voorbeelde, die aantoon van rededele en die byvoeging van etimologie kan gebruik word om die probleem van betekenisonder-skeiding in tweetalige Vendawoordeboeke op te los. Hierdie artikel beklemtoon die probleem van die afwesigheid van betekenisonderskeiding en dien oplossings in dié verband aan die hand vir toekomstige Vendaleksikograwe.Sleutelwoorde: TWEETALIGE WOORDEBOEK, BETEKENISONDERSKEIDING, EKWI-VALENSIE, TREFWOORD, LEKSIKOGRAFIE, KULTUUR, VERTALING, BRONTAAL, DOEL-TAAL, SINONIEM, POLISEMIES